STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK TUNA RUNGU DAN TUNA GRAHITA DI SEKOLAH LUAR BIASA NEGERI MUSI RAWAS - Ika Lathifah (IAIN Bengkulu, 2017)
The purpose of the study describes the learning strategy of Islamic education in the deaf children and the mentally disabled children as well as inhibiting factors and factors supporting the learning of Islamic religious education. This research is a qualitative research that is a field research that is descriptive. Data collection techniques: observation, interviews, and documentation. Data analysis techniques: data reduction, data presentation and conclusions. The result of this research is the learning strategy of Islamic education in deaf children is selected according to the needs of each student and the strategy used is the expository, inquiry, contextual teaching learning and individualization strategies and learning strategy of Islamic education in the mentally disabled children with more attention to the needs and capacity Ability of each student, strategy used, among others, active teacher learning strategy and individualization. The inhibiting factors found are not maximally the role of parents to teach the understanding of religion at home, the absence of special teachers Islamic education, students who have limitations that require a long process while the supporting factors are a comfortable learning environment, enthusiastic students, teachers who are creative in learning Islamic education, the principal who supports teaching and learning activities